Kajian Aplikasi Paclobutrazol dan Beberapa Jenis Pupuk Daun Terhadap Pertumbuhan Dan Produksi Tanaman Kentang (Solanum tuberosum L.) Dataran Menengah - Olke B. Lengkong; Eddy F. Lengkong; Diane F. Tiwow; Jemmy Najoan (Universitas Sam Ratulangi, 2015)
Abstract The study aims to know the effect of the timing of Paclobutrazol and complementary liquid fertilizer on the growth and yield of potato plains of medium and knowing the interaction between the timing of Paclobutrazol and other types of PPC. This research was conducted in October 2013 to January 2015 This study used factorial experiment with a randomized block design (RBD) consisting of: 6 combined treatment with 3 replications. Factor A: time paclobutrazol application on the age of the plant, namely A1 and A2 on the 30-day plant age 45 days. Whereas factor B: complementary liquid fertilizer consisting of B1: kristalon, B2: plant catalyst, B3: Gandasil D. Variables measured were plant height, amount of shoots, number of leaves, plant production and production samples perbedengan results showed that the results of research on Applications paclobutrazol significant effect on plant height, number of leaves, plant production and production samples of potatoes per plot and the number of shoots not significant. Interaction between the time of application of paclobutrazol and complementary liquid fertilizer does not give real influence. Keywords: organic C, Phosphorus, Potassium, Nitrogen, pH